A contação de histórias na extensão universitária e sua contribuição para a formação acadêmica - Silva, Carla Elisabete Cassel (2016)
The present study investigates the contribution of storytelling in the experience of extension students in the University Extension Project Conta Mais, focusing in storytelling in a public school, in the Toy Library, in the museum and in the kindergarten from the Federal University of Rio Grande do Sul (UFRGS). The historicity of the University Extension in Brazil and in UFRGS is presented in order to understand its goal and function in the context of higher education. The university extension projects that use storytelling in their activities are shown. This is a qualitative research built in the light of contributions from Bogdan and Biklen (1994), Lüdke and André (1986), and Minayo (2011). In order to complete this investigation, we chose an ethnographic-like case study, as taught by Lüdke and André (1986), and André (2008), as they understand that the ethnographic-like investigation makes it possible to investigate the contribution of storytelling in University Extension for the academic training of undergraduates in several areas of knowledge. Data collection was performed through semi-structured interviews with extension students, through participant observation in different locations where storytelling from Conta Mais Project happens, and through report analysis from the Conta Mais collection, based on the principles of document analysis. Data collected from the interviews was analyzed through Discursive Textual Analysis (DTA), which can be conceived as a self-organized process for the production of new understandings according to Moraes and Galiazzi (2011), relating the phenomena examined, linking them to theorical references and research purposes. In the analysis we interlaced narratives from academic extensions to the theoretical frameworks based on Benjamin (1987), Freire (1977) and Gadamer (1997). This investigation contributed to the field of Education, specifically to academic education, producing knowledge about a reality that is experienced in University Extension, which highlights the role of storytelling beyond schools, families and culture centers. Based on this study, it is possible to think that the experience of storytelling in the Conta Mais Project, from UFRGS University Extension, made the development of new ways of thinking and new ways of action possible to the undergraduates. This way, the Project contributed to the education per se, to the recognition and to the attribution of meanings and senses. This consideration can also add to the constant and innovating improvement of pedagogical practices in Extension, ratifying the importance of the inseparability of Extension, Education and Research, emphasizing, at the light of the opinion of extension students, the meaningful learning manifestations made during the performance and participation in a University Extension Project.